2014
DOI: 10.1086/678321
|View full text |Cite
|
Sign up to set email alerts
|

Forced to Be Bad: The Positive Impact of Low-Autonomy Vice Consumption on Consumer Vitality

Abstract: This research examines the vitality produced by vices-products that offer immediate gratification at the cost of long-term adversity. While vices are intrinsically enjoyable, they also induce guilt. Our conceptualization incorporates these opposing forces to argue that vice consumption is unique in that lowering the consumer's sense of autonomy actually results in higher vitality-in contrast to the positive relationship between autonomy and vitality that has been robustly documented in the literature. An exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 61 publications
2
29
0
12
Order By: Relevance
“…This resonates with recent research showing that satisficers, compared to maximizers, are more concerned about practical issues such as feasibility (Luan and Li 2017b). This finding also points to a potential boundary condition of self-determination theory, which is in line with recent research exploring such conditions (e.g., Abeyta et al 2017;Chen and Sengupta 2014). Finally, the current findings also have important managerial implications.…”
Section: Theoretical and Practical Contributionssupporting
confidence: 91%
“…This resonates with recent research showing that satisficers, compared to maximizers, are more concerned about practical issues such as feasibility (Luan and Li 2017b). This finding also points to a potential boundary condition of self-determination theory, which is in line with recent research exploring such conditions (e.g., Abeyta et al 2017;Chen and Sengupta 2014). Finally, the current findings also have important managerial implications.…”
Section: Theoretical and Practical Contributionssupporting
confidence: 91%
“…We document a novel antecedent of heightened vitality; namely, individuals who are currently feeling insufficient connectedness or competence can regain vitality simply by engaging in product anthropomorphism. Indeed, we hope that our focus on vitality drives further interest in this area; the construct of vitality has been largely underrepresented in the consumer literature (for a recent exception, see Chen and Sengupta 2014). This neglect is particularly surprising given the many positive consequences associated with vitality, such as task persistence, creativity, and even better health (Ryan and Frederick 1997;Penninx et al 2000;Chen and Sengupta 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that high vitality, among its other benefits, enhances regulatory strength, which then has a positive influence on subsequent self-control. In a recent study, participants who exhibited greater vitality after consuming intrinsically enjoyable "want" products versus extrinsically rewarding "should" products performed better on subsequent self-control tasks in unrelated domains (Chen and Sengupta 2014; see also Muraven et al 2008;Laran and Janiszewski 2011). Thus, vitality can be seen as the counterforce to depletion: experiencing a state of ego depletion impairs the ability to exert self-control later on (Baumeister et al 1998), whereas experiencing high vitality enhances subsequent self-control.…”
Section: Self-determination Theory and Vitalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Providing consumers with a limited sense of autonomy can thus, paradoxically, empower them and increase their well-being and motivation. For instance, choosing a dessert at a restaurant in which all the Bhealthy options^are out of stock will allow consumers to enjoy the full hedonic experience of a chocolate cake without the guilt that would be associated with an autonomous decision [17,25]. In the same way, acknowledging a limited sense of autonomy in others can have positive consequences and make people more forgiving: a weaker belief in free will has been shown to predict less retributive attitudes regarding punishment of criminals or other deviant behavior [58].…”
Section: Costs Of Experiencing Autonomy In Consumer Choicementioning
confidence: 99%